PREVENTION OF SHORTNESS OF BREATH AFTER PNEUMONIA - Urokova Vazira Khamidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. Pneumonia is a serious infectious disease that affects people of all ages. And children are no exception. Recently, there has been an increase in the number of acute infectious diseases of the respiratory system, and lung inflammation is the most dangerous of them. Therefore, parents should understand what it is – pneumonia, how to recognize this disease, and what to do in case of its occurrence in the child.